2016
DOI: 10.1111/bph.13549
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon‐like peptide‐1 receptor signalling reduces microvascular thrombosis, nitro‐oxidative stress and platelet activation in endotoxaemic mice

Abstract: This article is part of a themed section on Redox Biology and Oxidative Stress in Health and Disease. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v174.12/issuetoc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 51 publications
(64 reference statements)
6
76
0
Order By: Relevance
“…However, previous investigations have suggested that exendin‐4 and the DPP‐4 inhibitor, linagliptin, potentiate ACh relaxations in rat mesenteric arteries exposed to high glucose by a mechanism decreasing vascular superoxide levels (Salheen et al ., ). Also, native GLP‐1 decreased monocyte‐derived oxidative stress (Steven et al ., ). In the present study, a SOD mimetic, tempol, leftward‐shifted the concentration–response curves for ACh in arteries exposed to high glucose, suggesting vascular superoxide levels played a role in high glucose impairment of ACh relaxation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, previous investigations have suggested that exendin‐4 and the DPP‐4 inhibitor, linagliptin, potentiate ACh relaxations in rat mesenteric arteries exposed to high glucose by a mechanism decreasing vascular superoxide levels (Salheen et al ., ). Also, native GLP‐1 decreased monocyte‐derived oxidative stress (Steven et al ., ). In the present study, a SOD mimetic, tempol, leftward‐shifted the concentration–response curves for ACh in arteries exposed to high glucose, suggesting vascular superoxide levels played a role in high glucose impairment of ACh relaxation.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the effect on vascular tone of GLP‐1 is unclear, and a possible effect of GLP‐1 on the peripheral autonomic nervous system has not been examined despite the fact that several other gut‐derived peptides regulate the release of noradrenaline in the vasculature (Gradin et al ., ). Moreover, hyperglycaemia generates ROS which have been proposed to impair endothelium‐dependent relaxation, and growing evidence reveals that GLP‐1 receptor stimulation may reduce ROS (Salheen et al ., ; Steven et al ., ) and hence improve endothelial function (Salheen et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…DPP4i was reported to inhibit iNOS activity and iNOS-dependent NO production in a GLP-1 receptor dependent way in an LPS-septic model. The same study showed an inhibition of the NOX2isoform of NAPDH oxidase, with attenuation of ROS generation (24). DPP4i proved to reduce the inflammatory reaction by attenuation of the NF-κB p65 nuclear translocation and reduction of the release of inflammatory cytokines.…”
Section: Oxidative Stressmentioning
confidence: 71%
“…DPP4i reduces ROS production by NADPH oxidase production through the GLP-1/cAMP/PKA pathway in LPS-models (21,23,24). As NAPDPH oxidase plays © Annals of Translational Medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also provide an overview on the techniques used to measure endothelial dysfunction and on antioxidant strategies applied to prevent endothelial dysfunction and improve the associated cardiovascular diseases. Steven et al () show that glucagon‐like peptide‐1 supplementation and dipeptidyl peptidase‐4 inhibition (both new generation antidiabetic drugs) induce glucose‐independent anti‐inflammatory, antioxidant and anti‐thrombotic effects in mice with experimental sepsis. Xia et al .…”
mentioning
confidence: 99%